THE ROLE OF THE APPLICATION OF MODERN MILITARY TECHNOLOGICAL ACHIEVEMENTS IN ACHIEVING AZERBAIJAN'S MILITARY SUCCESS - Hafiz Musayev, (International Journal of Innovative Technologies in Social Science, 2023)
The article examines the role of the use of modern technologies in achieving the military successes of Azerbaijan. It explores the role of recent technological development in various spheres of society, especially achievements in the field of communications and information technology, the launch of three telecom¬munication satellites of Azerbaijan into orbit, production of products meeting high standards at enterprises of the Ministry of  Defense Industry, increasing the role of local production in providing our Army with weapons, as well as the role of modern technologies in achieving Azerbaijan's victory in the Patriotic War.The article uses such methods of studying socio-economic processes as specific-historical, comparative analysis, scientific generalization.